Symptomatic improvement after radiofrequency catheter ablation for typical atrial flutter. Issue 2 (1st August 2001) - O'Callaghan, P A; Meara, M; Kongsgaard, E; Poloniecki, J; Luddington, L; Foran, J; Camm, A J; Rowland, E; Ward, D E
Abstract : OBJECTIVE: To assess the changes in quality of life, arrhythmia symptoms, and hospital resource utilisation following catheter ablation of typical atrial flutter. DESIGN: Patient questionnaire to compare the time interval following ablation with a similar time interval before ablation. SETTING: Tertiary referral centre. PATIENTS: 63 consecutive patients were studied. Four patients subsequently underwent an ablate and pace procedure, two died of co-morbid illnesses, and two were lost to follow up. The remaining 55 patients form the basis of the report. RESULTS: Patients were followed for a mean (SD) of 12 (9.5) months. Atrial flutter ablation resulted in an improvement in quality of life (3.8 v 2.5, p < 0.001) and reductions in symptom frequency score (2.0 v 3.5, p < 0.001) and symptom severity score (2.0 v 3.8, p < 0.001) compared with preablation values. There was a reduction in the number of patients visiting accident and emergency departments (11% v 53%, p < 0.001), requiring cardioversion (7% v 51%, p < 0.001), or being admitted to hospital for a rhythm problem (11% v 56%, p < 0.001). Subgroup analysis confirmed that patients with atrial flutter and concomitant atrial fibrillation before ablation and those with atrial flutter alone both derived significant benefit from atrial flutter ablation. Patients with concomitant atrial fibrillation had an improvement in quality of life (3.5 v 2.5, p < 0.001) and reductions in symptom frequency score (2.3 v 3.5, p < 0.001) and symptom severity score (2.2 v 3.7, p < 0.001) compared with preablation values. CONCLUSIONS: Ablation of atrial flutter is recommended both in patients with atrial flutter alone and in those with concomitant atrial fibrillation.